ASPEK IBU HAMIL TERHADAP KEJADIAN HIPERTENSI - Utami, Rina; Gani, Kameriah; Umiyah, Astik; Resmi, Dewi Candra (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Hypertension or often known as high blood pressure is a medical condition characterized by a sustained increase in blood pressure in the blood vessels. Based on the Indonesian Health Profile in 2022, the number of deaths of pregnant women in 2022 reached 3,572 deaths. The province of South Sulawesi reached 195 cases. Takalar Regency is one of the districts in South Sulawesi. Takalar has 15 health centers and the highest hypertension rate is in Tanakeke Health Center. The Pattassang Health Center is the health center with the second highest case of hypertension in pregnant women. The general objective is to determine the aspects of pregnant women towards the incidence of hypertension. The research design used in this study is Case Control. The research was conducted at Pattallassang Health Center in June 2023. The study population was all pregnant women totaling 213 people. The sample amounted to 152 people. The sampling technique used purposive sampling. The research instrument used a research questionnaire. Data analysis was performed univariate and bivariate. The results showed a relationship between the age of pregnant women (p value: 0.000) and parity (p value: 0.037) to the incidence of hypertension in pregnant women. It is recommended that pregnant women should more regularly check or control blood pressure so that early signs of hypertension can be detected, especially for pregnant women who are <20 years old and >25 years old and have a history of previous pregnancies.Keywords: Hypertension, Parity, Age.